Emergence, Spread, and Characterization of Phage Variants of Epidemic Methicillin-Resistant Staphylococcus aureus 16 in England and Wales - Murchan, S. (J Clin Microbiol, 2004)
Epidemic methicillin-resistant Staphylococcus aureus 16 (EMRSA-16) and EMRSA-15 are the two most important and prevalent EMRSA strains found in the United Kingdom and have also been found in a number of European countries and the United States. We describe for the first time the spread of an EMRSA strain (EMRSA-16) from its point of origin in one hospital to the surrounding hospitals and regions over the following 2 years. In the first 18 months after its original appearance, 136 hospitals referred EMRSA-16 isolates for typing, and interhospital and intraregional spread were reported: it was more prevalent in males between 60 and 80 years old and was isolated from sputum and throat more often than EMRSA-15. Important characteristics, e.g., carriage of the enterotoxin A (sea) and toxic shock syndrome toxin (tst) genes and production of urease, are described. Phage-variant strains of EMRSA-16 which share some of the characteristics of the classical strain, including toxin carriage and urease production, emerged, but without genotypic investigations, their relationship could only be inferred. A total of 129 clinical isolates from 52 hospitals, collected between March 1998 and April 1999 and representing classical EMRSA-16 (49 isolates) or phage variants (80 isolates), were compared by phage typing, pulsed-field gel electrophoresis (PFGE) following SmaI macrorestriction, antimicrobial susceptibility testing, urease production, and PCR detection of toxin gene carriage. PFGE analysis revealed 29 profiles, A1 to A29, with A1 representing the prototypic strain, NCTC 13143. All other profiles differed from A1 by 1 to 6 bands, but some differed from each other by up to 10 bands.